Sámi Law: A Methodological Approach - Labba, Kristina (Arctic Review on Law and Politics, 2020)
Sámi law is the law of the Indigenous Sámi people. The territory where Sámi have historically lived is called Sápmi and encompasses parts of Norway, Sweden, Finland, and Russia. This article builds on the premise that Sámi law exists in Sápmi, in parallel with national laws. However, in terms of methodology and content, the scope of research on Sámi law compared to research about Indigenous law in Canada is limited. This article first describes an Indigenous law research methodology which approaches stories as a source of Indigenous law. The methodology was developed in Canada and applied to the Canadian Access to Justice and Reconciliation Project. The article then discusses this research methodology in relation to Sámi law.